Electronic and Bonding Properties of LiMn2O4 Spinel with Different Surface Orientations and Doping Elements and Their Effects on Manganese Dissolution. Issue 7 (1st January 2016) - Lee, Yoon Koo; Park, Jonghyun; Lu, Wei
Abstract : This paper investigates the effects of surface orientation and doping on the dissolution of Mn ions from LiMn2 O4 structures using first principles calculations. Our aim is to understand why certain surface orientations and element dopings produce structures with lower Mn dissolution. By comparing the electronic properties and structures of systems with different surfaces and dopings, Mn dissolution mechanisms and their prevention can be better understood. Based on our calculations, Mn dissolution is strongly correlated with the electronic and bonding properties of the Mn-O bonds. Surface orientations with a larger number of Mn-O bonds and smaller bond length require more energy to break the Mn-O bonds. In addition, doping with certain elements changes the bonding state of Mn, which either prevents or aggravates Mn dissolution.